Studi Agregat Faktor Pengetahuan dan Pemberian Vitamin A terhadap Prevalensi Stunting di Indonesia - Tianingrum, Niken Agus; Sari, Reny Mareta (Jurnal Dunia Kesmas, 2025)
Stunting has been being national nutrition problem that must be prioritized considering the importance of children's health and growth for a country. The study aims to analyze the variables of knowledge and correct attitudes towards all aspects about stunting and supplementation of High Dose Vitamin A related to the prevalence of stunting in 36 provinces in Indonesia. The study design was aggregate approach using SSGI 2024 data with province as analysis unit. Bivariate analysis was carried out using scatter plots and Kendall's tau correlation tests. The results of the study showed that most provinces in Indonesia still have a fairly high prevalence of stunting (14% - 21%). The results of the scatter plot and bivariate tests showed that the higher the proportion of knowledge and appropriate attitudes towards all aspects of stunting, the lower the prevalence of stunting. The higher the proportion of toddlers who received high doses of vitamin A in the last 12 months, the lower the prevalence of stunting. There is a relationship between the supplementation of vitamin A and the prevalence of stunting (p = 0.025 <0.05). It can be concluded that there is a positive relationship between high-dose Vitamin A supplementation and the prevalence of stunting. It is recommended that the policy maker support for areas with low coverage of Vitamin A supplementation.Stunting masih menjadi prioritas masalah gizi yang harus diprioritaskan mengingat pentingnya kesehatan dan pertumbuhan anak bagi suatu negara. Studi ditujukan untuk menganalisis variabel pengetahuan dan sikap yang tepat terhadap seluruh aspek stunting dan pemberian Vitamin A Dosis Tinggi yang berhubungan dengan prevalensi stunting di 36 provinsi di Indonesia. Desain studi menggunakan pendekatan studi agregat bersumber data SSGI 2024 dengan unit analisis adalah provinsi. Analisis bivariat dilakukan dengan menggunakan scatter plot dan uji korelasi Kendall’s tau.  Hasil penelitian menunjukkan sebagian besar provinsi di Indonesia masih memiliki prevalensi stunting yang cukup tinggi (14% – 21%). Hasil scatter plot dan uji bivariat menunjukkan bahwa semakin tinggi proporsi pengetahuan dan sikap yang tepat terhadap seluruh aspek stunting, maka semakin rendah prevalensi stunting. Semakin tinggi proporsi balita yang mendapatkan vitamin A dosis tinggi dalam 12 bulan terakhir, semakin rendah prevalensi stunting. Terdapat hubungan antara pemberian vitamin A dengan prevalensi stunting (p=0,025<0,05). Dapat disimpulkan bahwa terdapat hubungan positif antara suplementasi Vitamin A dosis tinggi dengan prevalensi stunting. Diharapkan pemangku kebijakan mampu mendorong peningkatan cakupan suplementasi vitamin A di provinsi yang masih rendah cakupannya.